Superconducting electromagnetic launch system for civil aircraft - Bertola, Luca; Cox, Thomas; Wheeler, Patrick; Garvey, Seamus D.; Morvan, Herve (Institute of Electrical and Electronics Engineers, 2016)
This paper considers the feasibility of different superconducting technologies for electromagnetic launch (EML) to assist civil aircraft take-off. EML has the potential of reducing the required runway length by increasing aircraft acceleration. Expensive airport extensions to face constant air traffic growth could be avoided by allowing large aircraft to operate from short runways at small airports. The new system positively affects total aircraft noise and exhaust emissions near airports and improves overall aircraft efficiency through reducing engine design constraints. Superconducting Linear Synchronous Motors (SCLSMs) can be exploited to deliver the required take-off thrust with electromagnetic performance that cannot be easily achieved by conventional electrical machines. The sizing procedure of a SCLSM able to launch A320 in weight is presented. Electromagnetic and thermal aspects of the machine are taken into account including the modelling of ac losses in superconductors and thermal insulation. The metallic high temperature superconductor (HTS) magnesium diboride (MgB2) is used and operated at 20 K, the boiling temperature of liquid hydrogen. With modern manufacturing technology, multifilament MgB2 wires appear to be the most cost-effective solution for this application. Finally the impact of the cryocooler efficiency on the machine performance is evaluated.